Worldwide Breeding and Commercialization of Edible Insects as anAlternative Source of Protein - Ortiz-Padilla, Wendy; Campos-Montes, Gabriel Ricardo; Cala-Moreno, Nelson; Caballero-Zamora, Alejandra (Spei Domus, 2024)
The increase in the world population has generated a greater demand for food production. In order to guarantee food security at a global level, an accelerated consumption of available for livestock production has been generated, such as the availability of land for agricultural use and water, in addition to negatively impacting the environment from the production of greenhouse gases. In this context, generating alternatives for protein production that are more sustainable than current production systems has become a priority. One of the proposed food alternatives is producing and consuming edible insects for human and animal nutrition. Edible insects stand out for their high nutritional content and potential to generate a lower environmental impact in controlled production than conventional livestock production. However, the development of controlled production of edible insects still requires answering questions about the safety and health of their products. This essay aims to summarize the current conditions of the production of edible insects in the nutritional, environmental, economic, legislative, and health and safety fields.
Keywords: entomophagy; protein; food safety; environmental impact